Physico-chemical Analysis of Selected Surface Water Samples of Laxmi Tal (Pond) in Jhansi City, UP, Bundelkhand Region, Central India - Raikwar1, Anshu Dhaka2; Minakshi3, Sandeep Arya1*, Vinit Kumar1, Madhullica (Journal of Experimental Sciences, 2011)
Laxmi Tall situated in Jhansi city located in Bundelkhand region of Central India, receive rain water as well as waste water from various nallas. Some physico-chemical parameters like temperature, pH, DO, BOD, COD, alkalinity, total hardness, Ca hardness, Mg hardness, and chloride were analyzed. Sampling of water was done during January to June 2010 from five different sites around the Laxmi Tall. Analytical results of the water have been observed as pH ranging from (7- 9.4), temperature (100C -320C), DO (0.89 -2.96 mg/l) l, BOD (2.8 -9.8 mg/l), COD (6.01 -24 mg/l), alkalinity (155 -355 mg/l), total hardness (323 -142 mg/l), chloride (4 -24 mg/l). The water shows alkaline nature throughout the year indicating highly polluted characteristics. The values of DO and BOD fluctuate according to seasons but a very low value of BOD/COD ratio was found, which represents high chemical pollution. From the observations, chloride and total hardness were recorded under permissible limit.